Association between the atherogenic index of plasma and testosterone deficiency in American adults: a cross-sectional study from NHANES 2011–2016 - Tai, Yanghao; Chen, Bin; Kong, Yingming; Shang, Jiwen (Frontiers in Endocrinology, 2025)
BackgroundA common pathophysiological association between lipid metabolism and sex hormone levels has been revealed in recent research. The atherogenic index of plasma (AIP) is the marker currently used to evaluate metabolism. The purpose of this research was to discover the relationship between the AIP and testosterone deficiency (TD) in a nationwide representative population.MethodsData from the National Health and Nutrition Examination Survey (NHANES) database from 2011 to 2016 were utilized in this cross-sectional research. The formula, lg [TG (mmol/L)/HDL-C(mmol/L)], was applied to determine the AIP. Total serum testosterone levels were used to define TD. Our researcher utilized smoothed curve fitting and multivariate logistic or linear regression analysis to inspect the relationship between AIP and TD among adult males. The consistency of these results was examined in various population subgroups.ResultsIn total, 1,198 individuals (28.6%) were stratified into the TD group. We observed statistically significant differences (P values < 0.05) in the TD population for all variables. After correcting for potential confounders, our researchers discovered a strong positive relationship between the AIP and the probability of developing TD. With each additional unit of the AIP, the incidence of TD increased by 2.81-fold in adult males. Subgroup analyses showed the correlations for the majority of the subgroups remained stable. However, marital status, CKD, smoking, and alcohol consumption may modify this association.ConclusionsA higher AIP is correlated with a lower level of testosterone in adult males. This correlation may be altered by factors including marriage, chronic kidney disease, alcohol, and smoking consumption.